ChemInform Abstract: Stereoselective Synthesis of the C1—C16 Fragment (VII) of Goniodomin A. Issue 3 (22nd January 2013) - Nakajima, Motohiro; Fuwa, Haruhiko; Sasaki, Makoto
Abstract involving the Stille‐type coupling of thioester (II) with vinylstannane (III) and spiroacetalization of diol mixture (V)/(VI) as the key steps